Anthropometric, aerobic and muscle power profile of young costa rican basketball players - Randall Gutiérrez-Vargas; José Alexis Ugalde-Ramírez; José Pino-Ortega; José Andrés Trejos-Montoya; Luis Blanco-Romero; Braulio Sánchez-Ureña; Juan Carlos Gutiérrez-Vargas; Daniel Rojas-Valverde (Universidad de Costa Rica, 2022)
The purpose of this study was to describe an anthropometric, aerobic and muscle power profile of young Costa Rican basketball players according to sex, play positions and age. The assessment was carried outa on 99 young players (43 women and 56 men; 18 guards, 51 forwards and 30 centers; 42 in the U16 category and 57 in the U18 category) from eight different teams. The sports experience of the players was 6.5 ± 3.1 years. The following parameters were assessed: height, weight, body mass index, skeletal muscle mass and body fat percentage, countermovement test (CMJ) and Yo-Yo Intermittent Recovery Test Level I. The main results showed significantly higher values in men than in women in terms of weight, height, skeletal muscle mass, distance covered in the yo-yo test, VO2max, height in CMJ and in flight time. Body fat percentage was higher in women than in men. Centers showed significantly higher height, weight and body fat percentage than other play positions. Guards and forwards covered more meters in the yo-yo test and showed higher VO2max than centers. No significant differences were found between the U16 and U18 categories in any variable. Regression models showed the influence of weight, body fat percentage, skeletal muscle mass and age on VO2max and CMJ. In conclusion, these indicators varied according to the sex and play position of the players. Additionally, this information will be useful for processes of promotion, development and training design of youth basketball in Costa Rica.